Packaging Consumption: Stylistic Devices and Persuasive Functions of American and Indonesian Advertising Slogans - Gabriella Tiara Utomo; Setefanus Suprajitno (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2018)
This study discusses the significance of style in creating indelible and iconic slogans that endures time. In this study, by using qualitative content analysis, I examine the stylistic devices of the ten American and Indonesian food and beverages slogans in order to find out their persuasive functions. In my analysis, I utilize three levels of stylistic analysis: phonological, lexical, and grammatical. My findings show that the most significantly used devices are the devices at the lexical level, then followed by those at grammatical and phonological level. My findings also show five recurring usages of the stylistic devices that help invoke the buying motives within the customers, namely idioms and proverbs, personification, humor, emotional appeal, and imagery. The usages serve a persuasive function by aided in influencing customers into purchasing the goods offered by the brand.